Screening of Trichoderma spp. isolates based on antagonism and chitinolytic index against Xylaria sp. - Wiwit Wicaksono Jati; Abdul Latief Abadi; Luqman Qurata Aini; Syamsuddin Djauhari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
Sugarcane disease disturbance is one of the limiting factors in achieving high productivity. Xylaria sp. has become endemic to sugarcane plantations in Lampung and South Sumatra. The intensity of disease attacks in Indonesia by 25% and 26% can reduce sugar production 12.3 and 15.4%, respectively. Losses due to disease attacks are greater in ratoons because plant cane sugarcane which is attacked by this disease, in ratoon stage, there will be a decrease in the number of shoots. The aim of this study was to obtain isolates of Trichoderma spp. which have antagonistic abilities and have chitinase enzymes so that they are effectively used as biological agents against Xylaria sp. The research method of antagonist test used dual culture test and qualitative test of chitin substrate was used to assess the chitinolytic index of four isolates of Trichoderma spp. The parameters were the inhibition of Trichoderma spp. isolates and the chitinolytic index of the four isolates moreover the value of the chitinase enzyme activity of the selected isolates. Mechanism of antagonist T10 are competition, antibiosis and mycoparasitism. The results showed that the Indonesian Sugar Research Institute (ISRI) T10 isolate could be used as a biological agent against Xylaria sp. The isolate had an inhibitory ability 73.33% with a chitinolytic index value 1.15 and the activity value of the chitinase enzyme crude extraction at a dilution 10-1 was 10.99 units/mL.